The practice of occupational therapists with people living with HIV/AIDS (Research, Society and Development, 2024)
People with HIV experience harm to their health and functionality, with negative impacts on their occupational performance. The objective of this study was to describe the work of occupational therapists with people living with HIV/AIDS. A narrative review was carried out, based on scientific literature and Brazilian and Latin American Occupational Therapy journals. 13 articles were included, between 2003 and 2018, with more publications from Brazil and referring to Occupational Therapy activities with hospitalized adults. The HIV/AIDS causes physical, cognitive, emotional, neurological and psychosocial difficulties, affecting self-care, leisure, school and work activities. Living with HIV/AIDS distances people from their professional and social roles. Occupational Therapy aims to reestablish better conditions for activities of daily living, health care and coping with social problems. The occupational therapist's work explores strategies with artistic and expressive activities, in groups, workshops and outpatient or hospital care. The professional works, according to the needs of the clientele and the context, to encourage reflection and empowerment of people with HIV/AIDS in recognizing their rights, facing discrimination and limitations of social participation. Occupational therapists also support family members, the school staff and the community in interacting with and respecting people with HIV/AIDS. It is concluded that the Occupational Therapy intervention seeks to restore occupational performance and quality of life, not only for those living with HIV/AIDS, but for those who live with these people.